Specific Aspects of The Analysis of The Natural-Geographical Characteristics of The Lower Zarafshan District on The Base of Gat Technologies - Begjan Khusanov; Anvar Rasulov (European International Journal of Pedagogics, 2025)
This article discusses the issues of assessing the natural components of the Lower Zarafshan physical-geographical district using geoinformation technologies (GIS). The main focus is on the interrelationships of natural components such as relief, climate, water resources, soil and vegetation cover, and their spatial analysis. GIS technologies allow for the systematization, analysis and visualization of large volumes of natural data. This article is aimed at forming scientifically based conclusions that will serve the effective use, protection and sustainable development of natural resources in the region.